Multicountry survey of emergency and critical care medicine physicians’ fluid resuscitation practices for adult patients with early septic shock - McIntyre,L; Rowe,BH; Walsh,TS; Gray,A; Arabi,Y; Perner,A; Gordon,A; Marshall,J; Cook,D; Fox-Robichaud,A; Bagshaw,SM; Green,R; et al. (BMJ Open, 2016)
Objectives: Evidence to guide fluid resuscitationevidence in sepsis continues to evolve. Weconducted a multicountry survey of emergency andcritical care physicians to describe current statedpractice and practice variation related to thequantity, rapidity and type of resuscitation fluidadministered in early septic shock to inform thedesign of future septic shock fluid resuscitationtrials.Methods: Using a web-based survey tool, weinvited critical care and emergency physicians inCanada, the UK, Scandinavia and Saudi Arabia tocomplete a self-administered electronic survey.Results: A total of 1097 physicians’ responseswere included. 1 L was the most frequent quantityof resuscitation fluid physicians indicated theywould administer at a time (46.9%, n=499). Most(63.0%, n=671) stated that they would administerthe fluid challenges as quickly as possible. Overall,normal saline and Ringer’s solutions were thepreferred crystalloid fluids used ‘often’ or ‘always’ in53.1% (n=556) and 60.5% (n=632) of instances,respectively. However, emergency physiciansindicated that they would use normal saline ‘often’or ‘always’ in 83.9% (n=376) of instances, whilecritical care physicians said that they would usesaline ‘often’ or ‘always’ in 27.9% (n=150) ofinstances. Only 1.0% (n=10) of respondentsindicated that they would use hydroxyethyl starch‘often’ or ‘always’; use of 5% (5.6% (n=59)) or 20–25% albumin (1.3% (n=14)) was also infrequent.The majority (88.4%, n=896) of respondentsindicated that a large randomised controlled trialcomparing 5% albumin to a crystalloid fluid in earlyseptic shock was important to conduct.Conclusions: Critical care and emergencyphysicians stated that they rapidly infuse volumes of500–1000 mL of resuscitation fluid in early septicshock. Colloid use, specifically the use of albumin,was infrequently reported. Our survey identifies the need to condu